ANALYSIS OF THE POTENTIAL OF VIRTUAL LAB RESEARCH DEVELOPMENT IN SCIENCE LEARNING WITH THE BIBLIOMETRIC METHOD - Meili Yanti; Dea Santika Rahayu; Haryanti Putri Rizal (Science Education, Institut Agama Islam Negeri Ponorogo, 2023)
The development of scientific fields is possible through communication between researchers. This communication can be established with a medium called the Scientific Journal. Through the media, each researcher searches for articles that have been researched on the same topic. So that they will easily update or develop the topic. This method is known as the bibliometric analysis method. Therefore this study aims to carry out the same analysis on the virtual lab theme. This is important in learning development, especially in science learning. The data obtained was in the form of many articles from the SCOPUS database, which several criteria had previously defined to capture them. These criteria are related to the year of publication, keywords and language selection. The application used in this study is the VOS Viewers application. The results show that research related to virtual labs in science learning is still very possible considering many limited lab facilities in some schools. However, it should be noted that virtual labs cannot replace traditional laboratories because traditional laboratories can give students hands-on practical experience. It is better if the virtual lab is considered as a supplementary to science learning